Examining sociology's position in an increasingly interdisciplinary environment - Žažar, Krešimir (Družboslovne razprave, 2016)
The perspective of growing interdisciplinarity implies the need to establish sociology's position within an even more "interdisciplinary environment" of contemporary science. Sociology's relationship with other sciences is intimately intertwined with several types of issues scrutinised here: a) the modalities of interdisciplinary conjunctions; b) the attributes of levels at which interdisciplinary cooperation may appear; c) what sociology can provide to and what it may require from other disciplines; and d) potential advantages of participation in interdisciplinary scientific ventures, as well as their possible hazards. Further, the preference for multidisciplinarity as a "softer" variant of interdisciplinary connection is emphasised. Finally, the urgency pertaining to the disciplinary uniqueness of sociology, due to its capability to adequately answer a vast number of social challenges today, is underlined.
Keywords: Sociologija; Sociology; Interdisciplinarnost; Interdisciplinary approach to knowledge; Scientific areas; Znanstvene discipline